FORMATION OF ORGANIZATIONAL AND ECONOMIC MECHANISM OF RESIDENTIAL FUND - MALIAR, STANISLAV (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Ensuring the economic security of residential fund owners should be based on an organizational and economic mechanism designed to manage financial, labor, and other resources to improve the reliability of critical household systems, prevent accidents due to destruction or inefficient systems. thus, an important condition for ensuring an effective process of residential fund management is the introduction of an organizational and economic mechanism for residential fund development. Considerable attention is paid to the development of the residential fund. Despite the significant amount of research related to the development of residential fund, the issue of forming the organizational and economic mechanism of residential fund development remains unresolved. The purpose of the article is to form an organizational and economic mechanism for residential fund development. It is established that the organizational and economic mechanism of residential fund development is a complex system of organizational and economic elements aimed at organizing interaction between elements of the system to improve the reliability of critical systems, prevent accidents due to destruction or inefficient work, considering external and internal environment. The article proposes the organizational and economic mechanism of residential fund development. Its main constituent subsystems are given: subsystem of influence of internal and external environments; control subsystem; managed subsystem; control subsystem; implementation subsystem. the proposed organizational and economic mechanism of residential fund development, in contrast to existing ones, considers the reliability of critical systems of the internal infrastructure of residential buildings based on a model based on the theory of fuzzy logic and linguistic variable. The mathematical model allows to consider the quantitative and qualitative factors of the critical infrastructure of the house on the development of housing.